2018
DOI: 10.1002/htj.21370
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on conventional solar still integrated with inclined solar still under different water depth

Abstract: This study primarily focuses on comparative experimental analysis on standalone conventional solar still (CSS), inclined solar still (ISS), and integrated conventional and inclined solar still (CSS‐ISS) for different parameters that affect the freshwater yield. For enhancing the freshwater yield only a few studies are available on still‐still integration. The present novel study provides a greater improvement in improving the freshwater yield by integrating ISS with CSS. This experimental work mainly concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
2
13
0
1
Order By: Relevance
“…Table shows the uncertainty analysis, and equations for analysis are shown in Appendix . Table shows the error analysis of various measuring instruments used in present research work …”
Section: Experimental Set‐upmentioning
confidence: 99%
See 2 more Smart Citations
“…Table shows the uncertainty analysis, and equations for analysis are shown in Appendix . Table shows the error analysis of various measuring instruments used in present research work …”
Section: Experimental Set‐upmentioning
confidence: 99%
“…Table 3 shows the error analysis of various measuring instruments used in present research work. 8 4 | RESULTS AND DISCUSSION…”
Section: Preparation Of Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Any change in solar radiation affects solar distillation. Climate change or seasonal changes directly affect productivity, which has been proven by studies and real‐life experiments . Other studies were based on improving the productivity of the single slope by several simple and cheap methods .…”
Section: Introductionmentioning
confidence: 99%
“…Different review articles have been studied . Various research works have reported the use of nanofluid in solar still, the conventional solar still (CSS) with energy storage materials, inclined solar still, and hybrid solar still …”
Section: Introductionmentioning
confidence: 99%